Study on simulation effect of physical and chemical characteristics of sausage by sausage model system - Ji, Lili; Zhou, Chunyan; Zhou, Yanan; Nie, Qing; Luo, Yi; Yang, Rui; Wang, Shu; Ning, Jiawen; Zhang, Jiamin; Zhang, Ying (Frontiers in Nutrition, 2024)
The physicochemical indexes and the quantity of flavoring components in the model and sausage with and without the inclusion of Staphylococcus xylosus were assessed in order to evaluate the effect of the sausage model on the simulation of the physicochemical features of sausage. The findings demonstrated that there were comparable alterations in the Staphylococcus xylosus indexes between the sausage and the model. The pH and Aw in both the model and sausage were not significantly affected by Staphylococcus xylosus; however, there was a considerable increase in the content of volatile flavor compounds, particularly esters and aldehydes, which were significantly higher than those in the control group. Meanwhile, the TBARS value of each experimental group at the end of the test was significantly lower than that of the control group. This demonstrates how Staphylococcus xylosus can inhibit fat oxidation and encourage the synthesis of flavoring compounds. The sausage model can better represent an environment for in vitro research on sausage by simulating the index responses of pH, TBARS, Aw, and flavor, reflecting similar tendencies.